1998
DOI: 10.1063/1.367420
|View full text |Cite
|
Sign up to set email alerts
|

Study on growth processes of particles in germane radio frequency discharges using laser light scattering and scanning electron microscopic methods

Abstract: Effects of micro-and macro-plasma-sheath electric fields on carbon nanotube growth in a cross-field radiofrequency discharge Determination of the size, optical index and density of particles in an argon-silane radio-frequency discharge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…(These narrow size distributions are typically referred to as monodisperse though all nanoparticle population distributions always have a finite width.) Yet many experimental studies have strongly suggested that under some conditions coagulation in nonthermal plasmas does indeed occur. ,, …”
Section: Fundamentals Of Nonthermal Plasmasmentioning
confidence: 99%
“…(These narrow size distributions are typically referred to as monodisperse though all nanoparticle population distributions always have a finite width.) Yet many experimental studies have strongly suggested that under some conditions coagulation in nonthermal plasmas does indeed occur. ,, …”
Section: Fundamentals Of Nonthermal Plasmasmentioning
confidence: 99%
“…Coagulation coefficients (effectively, rate constants) for coagulation between particles of dissimilar sizes are largerand as the size dissimilarity increases, they become much larger-than for coagulation of same-sized particles. While Coulombic repulsion between unipolar negatively charged particles may in most cases make coagulation insignificant for dusty plasmas containing micrometer-size particles, a number of studies have indicated that coagulation is important in nanodusty plasmas [11,24,[28][29][30][31][32][33][34]. And, unlike the case in neutral aerosols, the charge states of particles are obviously of crucial importance for coagulation rates.…”
Section: Introductionmentioning
confidence: 99%
“…Powder growth in SiH 4 discharge takes place in the time scale of the order of seconds [8]. In GeH 4 discharge there are reports of faster growth (order of tens of milliseconds) of the observable powders within the plasma [9]. Our study revealed a quite important observation that the powder formation within a discharge containing GeH 4 is even faster.…”
Section: Discussionmentioning
confidence: 67%